2016
DOI: 10.1186/s13059-016-1101-2
|View full text |Cite
|
Sign up to set email alerts
|

Functional and regulatory profiling of energy metabolism in fission yeast

Abstract: BackgroundThe control of energy metabolism is fundamental for cell growth and function and anomalies in it are implicated in complex diseases and ageing. Metabolism in yeast cells can be manipulated by supplying different carbon sources: yeast grown on glucose rapidly proliferates by fermentation, analogous to tumour cells growing by aerobic glycolysis, whereas on non-fermentable carbon sources metabolism shifts towards respiration.ResultsWe screened deletion libraries of fission yeast to identify over 200 gen… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
59
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 55 publications
(62 citation statements)
references
References 89 publications
(119 reference statements)
3
59
0
Order By: Relevance
“…We have shown that antimycin A, an inhibitor of the respiratory chain, slows down the growth of S. pombe cells in defined minimal medium, but much less so in rich yeast extract medium with the same glucose concentration [35] (Fig. S1A).…”
Section: Arginine Supplementation Is Necessary and Sufficient For Rapmentioning
confidence: 91%
See 1 more Smart Citation
“…We have shown that antimycin A, an inhibitor of the respiratory chain, slows down the growth of S. pombe cells in defined minimal medium, but much less so in rich yeast extract medium with the same glucose concentration [35] (Fig. S1A).…”
Section: Arginine Supplementation Is Necessary and Sufficient For Rapmentioning
confidence: 91%
“…The S. pombe laboratory strain is part of a group of natural isolates that show higher respiration during fermentative growth, which is caused by a naturally occurring mutation in pyruvate kinase that limits glycolytic flux [34]. We have also reported that respiration is required for rapid cell proliferation during fermentation [35]. Here we define the respiratory functions in fission yeast that support rapid proliferation.…”
Section: Introductionmentioning
confidence: 97%
“…The pdc101 and atd1 genes, on the other hand, were expressed more highly in the A-strain. These genes encode pyruvate decarboxylase and aldehyde dehydrogenase, respectively, and their induction is consistent with higher glycolytic flux and increased fermentation 29 . These expression changes are consistent with the central role of PYK in glycolysis and the observed metabolic effects mediated by the Pyk1 variants.…”
Section: Increased Pyk Activity Leads To Transcriptome and Proteome Cmentioning
confidence: 61%
“…Resistance to antimycin A, which blocks the respiratory chain by inhibiting ubiquinol-cytochrome c oxidoreductase 42 , was used as a proxy readout for cellular dependence on oxidative phosphorylation. The standard laboratory strain 972 hshows a moderate reduction in maximum growth rate and biomass yield in this condition 29,43 . We applied a colony-based assay to determine relative fitness of each strain in rich glucose media with and without antimycin A.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation